A critical review of parameters governing the boiling characteristics of tube bundle on shell side of two-phase shell and tube heat exchangers. (1st March 2022) - Moharana, Subhakanta; Bhattacharya, Anirban; Das, Mihir Kumar
Highlights: Effect of parameters governing shell side HTC in two-phase heat exchangers. Flow boiling, pool boiling and flow regime studies for tube bundles. Heat flux, mass flux, vapour quality, pressure and pressure drop effects analysed. Importance of tube parameters, tube arrangement, and enhanced tube considered. Abstract: Heat transfer by the process of boiling is advantageous due to the high heat transfer coefficient associated with the process. In many heat transfer applications, boiling on tubes and tube bundles are encountered. Tube bundle studies are important as these are an integral part of shell and tube heat exchangers, reboilers, evaporators used commercially both in industrial and non-industrial applications. Similarly, tube bundles with vertical configuration are integral part of nuclear reactors. In this review, the effects of different parameters affecting heat transfer in tube bundles on the shell side of two-phase shell and tube heat exchangers are analysed based on available literature. The studies included are subdivided into effect of performance parameters for flow boiling and for pool boiling. The pool boiling heat transfer devices do not require any active flow equipment, whereas in case of flow boiling active flow equipment is essential for continuously supplying the working fluid. In order to design an effective heat exchanging device having tube bundles the combined effect of parameters such as heat flux, mass flux, quality, tube geometry, spacing etc. need to be considered. This article highlights various critical parameters, considered by studies available in the open literature, which affect the heat transfer in two-phase flow heat exchanging devices.